Incidencia del clima del aula en el rendimiento académico en estudiantes de bachillerato en la unidad educativa quevedo en el periodo 2024-2025 - Palacios Delgado , Alex Dario (2025)
The study on the relationship between classroom climate and academic performance among high school students aimed to analyze how classroom climate influences academic outcomes during the 2024-2025 period. A quantitative approach was used, employing a non-experimental and correlational research design. The sample consisted of 180 students who completed classroom climate questionnaires and standardized tests to assess their academic performance in key subject areas. The results indicated that the classroom climate was mostly perceived as positive; however, no significant relationship was found with academic performance. Correlation tests revealed a weak and statistically non-significant association between the two variables, suggesting that factors such as motivation and teaching strategies have a greater influence on student performance. Despite these findings, the study concluded that classroom climate remains an important factor for students' well-being and emotional development, even if it does not always directly impact their academic performance. It was recommended that future studies explore other factors influencing educational outcomes and enhance pedagogical and management strategies to foster a more positive and motivating learning environment. This approach would continue to support students' holistic development, ensuring a balance between emotional and academic conditions that promote better performance.